Agreement of results between dry and wet chemistry system for common clinical chemistry parameters (Journal of Pathology of Nepal, 2023)
Background: The advancement of analytical chemistry has led to the use of automated systems in clinical laboratories, including liquid-based wet chemistry and film-based dry chemistry systems. Reflectance spectrophotometry-based dry chemistry systems offer a viable alternative to wet chemistry analyzers. This study aimed to compare the agreement of results between the dry chemistry system and the wet chemistry system.Materials and Methods: Secondary data from external quality control samples were analyzed using the Vitros 350 and BA-400 analyzers, over a period of one year (from 1st August 2021 to 31st July 2022). A total of 57 samples and 12 biochemical parameters were considered. Statistical analysis, including paired t-tests, Spearman's correlation, Bland-Altman plots, and the Intraclass Correlation Coefficient were applied. p value